2023
DOI: 10.20944/preprints202306.0456.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hepatitis E Virus Infections

Busara Songtanin,
Adebayo J. Molehin,
Kevin Brittan
et al.

Abstract: According to the World Health Organization, approximately 20 million people worldwide are infected annually with the hepatitis E virus (HEV). There are 4 main genotypes of HEV. Genotype 1 and genotype 2 are common in developing countries and are transmitted by contaminated water from a fecal-oral route. Genotype 3 and genotype 4 are common in developed countries and can lead to occasional transmission to humans by undercooked meat. Hepatitis E virus 1 and HEV3 can lead to fulminant hepatitis, and HEV3 can lead… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 125 publications
0
2
0
Order By: Relevance
“…SN 2022xkq is located near the edge of a weak spiral arm, 49 91 W and 38 63 S of the center of its host galaxy (see Figure 1 in Pearson et al 2024). Underluminous SNe Ia are typically found in older stellar populations, and thus more likely to occur in elliptical galaxies (Branch et al 1996;Hamuy et al 1996;Howell 2001;Sullivan et al 2010;Ashall et al 2016a;Nugent et al 2023); although old stellar populations can also be found in late-type spirals such as NGC 1784. Interestingly, the underluminous SN 1999by was also discovered in a late-type spiral (Howell 2001;Garnavich et al 2004), and shows some properties similar to those of SN 2022xkq (Pearson et al 2024).…”
Section: Early Observations Of Sn 2022xkqmentioning
confidence: 99%
“…SN 2022xkq is located near the edge of a weak spiral arm, 49 91 W and 38 63 S of the center of its host galaxy (see Figure 1 in Pearson et al 2024). Underluminous SNe Ia are typically found in older stellar populations, and thus more likely to occur in elliptical galaxies (Branch et al 1996;Hamuy et al 1996;Howell 2001;Sullivan et al 2010;Ashall et al 2016a;Nugent et al 2023); although old stellar populations can also be found in late-type spirals such as NGC 1784. Interestingly, the underluminous SN 1999by was also discovered in a late-type spiral (Howell 2001;Garnavich et al 2004), and shows some properties similar to those of SN 2022xkq (Pearson et al 2024).…”
Section: Early Observations Of Sn 2022xkqmentioning
confidence: 99%
“…As shown in Figure 1, 55 SN 2022xkq is located in NGC 1784, a barred spiral SB(r)c galaxy (de Vaucouleurs et al 1991;Erwin & Debattista 2013) and SN 2022xkq is the first recorded SN in the galaxy. Underluminous SNe Ia preferentially explode in older galaxy populations and are most likely to be found in elliptical and occasionally in earlytype spiral galaxies (Hamuy et al 2000;Howell 2001;Gallagher et al 2005;Sullivan et al 2006;Li et al 2011;Nugent et al 2023). However, late-type spiral galaxies also possess old stellar populations, and while underluminous SNe Ia in late-type hosts are uncommon, there have been a few.…”
Section: Discoverymentioning
confidence: 99%